Deteksi Dominasi Warna Potongan Citra Sebagai Mesin Puzzle Digital - Agustinus Rudatyo Himamunanto; Haeni Budiati (Journal of Information Technology, 2022)
Puzzle is a game of rearranging pieces of picture objects, which can train creativity, order, and concentration levels. Problems in puzzle games will be more complicated when the size of the pieces gets smaller so that the number of pieces increases. The challenge is how to always make new puzzle arrangements and quickly reassemble recovery pieces. The focus of this research is to arrange puzzle pieces randomly and try to reposition the puzzle using the proposed method, namely DCD (Dominant Color Detection). The DCD method works by using the color histogram method to track the image based on the dominant color information. The Eucledian Distance method is then used to measure the level of image similarity . The similarity indication of the puzzle image is used to reposition the puzzle. Based on the test results, it is known that the accuracy of the repositioning results on the sample logo image, totaling 30 test images, is 100% successful in getting the whole image back according to the logo input image. This method has the opportunity to be used as an alternative to access security and also as a simple engine model for image search based on image fragments.